Surgical management of necrotizing fasciitis due to odontogenic infection with sepsis: a case report - Saka S. Nugroho; Endang Syamsudin; Andri Hardianto; Lucky Riawan (DiscoverSys Inc., 2017)
Objective:To perform surgical operation on necrotizing fasciitis due to odontegenic infection with sepsis.Methods: In this case an odontogenic infection was accompanied by a large open wound on the face and sepsis. Patient was hospitalized in the Dr.HasanSadikin General Hospital. Management of this patient in the emergency room were administration of appropriate broad-spectrum empiric antibiotic, incision and pus drainage, and extraction of the infected tooth, followed by fluid resuscitation with strict observation. Surgical debridement was then performed.Results:After being treated for 12 days the patient’s condition improved. We planned closure of defects of the facial area, but the patient refused.Conclusion: Necrotizing fasciitis is an uncommon but potentially lethal condition associated with high rates of morbidity and mortality. Early diagnosis coupled with emergent surgical debridement, appropriate broad-spectrum empiric antibiotic treatment, and a multidisciplinary team approach is essential for successful treatment.